El cuidado transicional de enfermería aumenta la compentencia en el rol del cuidador del niño con cáncer - Carreño Moreno, Sonia (Psicooncología, 2017)
Introduction. The family caregiver of child with cancer goes through a transition in their role in strengthening competence required to exercise it. Objective. To determine the effect of an intervention of transitional nursing care on the competency of the family caregiver of a child with cáncer. Methodology. Experimental study, the experimental group (n=59) underwent an intervention developed by the investigators “Taking care of our children with cancer”, the control group (n=59) received usual care. It was measured the competency of care of the caregiver, it was a double-blind study. The analysis was performed using the Student’s t test, the effect size was estimated using average exchange standardized difference - d Cohen. Results. Most of the children were diagnosed with leukemia 41% and the average age was 4 years. Family caregivers are women 84%, mean age 33. A competency of care difference (p <0.001) was observed in the posttest, with an effect size d = 5.14 Conclusion. The intervention “Caring for our children with cancer” has strong effect increasing the competency of care of family caregiver in the transition process of their role. The intervention is applicable to practical and replicable in the investigation.